Structured academic writing retreats in healthcare professional practice. (19th October 2020) - Bell, Mary; Murray, Rowena
Abstract: The critical importance of writing skills in communicating issues, such as the evidence needed for resources and change as well as the implementation of new practices and processes based on evidence‐based outcomes, are now core skills for every healthcare professional including nurses in clinical practice. Within a very busy and challenging work environment, while maintaining a work–life balance, writing to fulfil these professional requirements can become challenging and even impossible. This article describes an educational intervention which adopted the Structured Writing Retreat (SWR) model developed by Murray and Newton in 2009 into a healthcare practice setting. The aim of this intervention was to promote self‐efficacy in academic writing in a supportive environment. Three tools are described which outline how to set this intervention up within a healthcare setting. The outcomes and participants' evaluations clearly affirmed the benefits of this model to enable healthcare professionals working in any clinical environment to support their professional development and career advancement.